Relações Intergovernamentais: o uso de dois pesos e duas medidas na construção dos Pactos de Aprimoramento do SUAS - Ana Carolina de Souza (2016)
This research report discusses as a central theme the intergovernment relationships, addressed in the realm of the brazilian Social Assistance Unified System (SAUS), as regards the SAUS Improvement Pacts. In this research, we aimed to understand the relationships among federative entities in Brazil (Federal government, state governments and municipalities) on the construction of these mechanisms, having as a premise the fact that the agréments are a result of the deliberative process taken in a consensual decision sphere (the Tripartite Intermanagers Comission TIC). We assume that the Agreements shape intergovernment coordination mechanisms, and, thus, seek cooperation in executing the Social Assistance policies. However, as a result of a primary investigation of these mechanism, we observe that there is some imbalance regarding the powers of each one of the subnational entities (State governments and municipalities), which are, at first, equally responsible for implementing these policies. Relying on theories that discuss federalism and intergovernment relationships, we have performed a qualitative content analysis, in which we have used transcriptions from the TIC meetings. Our analytical emphasis was on the following aspects: I) intergovernment relationships developed in the realm of TIC; II) the roles addressed to each federative entity on the Agreement wording; III) the goals and priorities addressed to the federative entities. Our results show that there is an inner negotiation process in course in the Comission, as regards the Improvement Pacts. In these negotiation processes, we couldnt find coercitive relationships among brazilian Federal government, state governments and municipalities. The unbalance of the goals hasnt been unnoticed by the federative entities that took part in the Improvement Pact. Having this in mind, in order to stimulate further inquiry that complement our research, we rediscuss some hypotheses.